Beneficial Microorganisms in Agriculture, Aquaculture and Other Areas - Liong, Min-Tze.; Liong, Min-Tze. (Microbiology Monographs, 2015)
This book focuses on the use of microorganisms in relation to agriculture, aquaculture and related fields, ranging from biofertilizers to poultry production. The latest innovations are also included to provide insights into the unlimited potentials of microorganisms in these areas. Individual chapters explore topics such as probiotics in poultry, biopurification of wastewater, converting agrowastes into value-added applications and products, rice cultivation, surfactants and bacteriocin as biopreservatives, bioplastics, crop productivity, biofloc, and the production of natural antibiotics. This volume will be of particular interest to scientists, policymakers and industrial practitioners working in the fields of agriculture, aquaculture and public health.